ANALYSIS OF THE CAUSES OF CAMEROON'S PERMANENT DEPENDENCE ON RICE IMPORTS - Pierre Bertran MBONDJI NTOMBE; Fon Dorothy ENGWALI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study, which aims to analyze the causes of Cameroon's permanent dependence on rice imports, is inspired by the observation that the expense linked to rice imports has a very negative influence on the Cameroonian trade balance; however, the country produces rice which is mainly exported to certain neighboring countries. To carry out this study, the objectives were set to analyze the marketing channels of Cameroonian rice, and to identify the factors that favors rice consumption. The target populations are traders and consumers of rice in Cameroon. The regions covered are those of the Far North, North, and Center, which produce most of the rice in Cameroon. To collect data in the field, questionnaires and interview guides were developed. As for the traders, an interview guide was used to collect information, after carrying out a categorization. For this purpose, local wholesalers of paddy rice, foreign wholesalers of paddy rice, foreign wholesalers of processed rice, retailers of markets close to production areas, local wholesalers of processed rice, wholesale retailers, supermarkets, and shopswere identified. At the consumer level, populations residing in production areas, populations in metropolises close to production areas, and populations in metropolises far from production areas were identified. The data collected was analyzed using software such as SPSS and Excel spreadsheet. The tables and figures made it possible to clearly present the results, and thus facilitate their interpretation. It therefore appears that wholesalers of paddy rice who sell it directly to foreign buyers, making a gross margin for an 80 kg bag which varies between 2,000 and 3,000 FCFA, while those who process before reselling on the local market make barely a margin of 500 FCFA. In addition to this observation, we observe that wholesalers of processed rice who sell their products in metropolises far from the production basins have a gross margin which is completely double that observed in the metropolises close to the production basins; which is justified by the presence of intermediaries, and the transport costs necessary to ensure the transition of rice from production areas to consumption centers. The results show that 43.2% of Cameroonians consume on average kg of rice per day; but unfortunately, most are not aware of the existence of locally produced rice, and even those who are aware of it cannot easily find it on the market. In the metropolises of the southern zone of Cameroon, for example, we have around 50% of the population who are not aware of the fact that there is rice produced in Cameroon, 30% of the population who are informed but never had the opportunity to consume it.In view of all these parameters, Cameroonian rice is oriented primarily towards neighboring countries which are closer to the production basins, while the country continues to import rice from outside to satisfy the needs of its populations.